Burden of respiratory problems in low-income and middle-income countries. Issue 4 (13th December 2022) - Clark, Joseph; Kochovska, Slavica; Currow, David C.
Abstract : Purpose of review: Chronic respiratory diseases are a leading cause of morbidity and mortality in low-income and middle-income countries (LMICs). We aim to review prevalence of respiratory diseases and related symptoms, which contribute significantly to burden of disease in LMICs. We report global estimates of respiratory problems amongst adults in LMICs and recent findings relating to community prevalence and impact of respiratory problems. We conclude by identifying research priorities for improved recognition and palliation of respiratory problems. Recent findings: We report findings from 16 studies, highlighting key issues relevant to burden of respiratory problems in LMICs. COPD and associated symptoms are identified as important drivers of increasing respiratory problems in LMICs, with an estimated prevalence of 7.2%. Negative impacts of respiratory diseases include: reduced physical function (capacity to work), quality of life (depression; anxiety) and socioeconomic wellbeing (healthcare costs; earning potential). Locally appropriate palliative care interventions may improve quality of life without increasing costs. Summary: Prevention and treatment of respiratory diseases is essential for improved wellbeing. We identify missed opportunities for measurement and understanding of burden caused by respiratory problems within efforts to measure illness prevalence. We highlight need for symptom management interventions, developed in context of local cultural beliefs and behaviours.